Aplicação de recursos de gestão produtiva total (TPM) para gestão de ativos em empresas de distribuição de energia elétrica - Gissoni, Roger Toledo (2016)
Given the current economic scenario experienced by companies in the Brazilian energy sector and for having intensive reliance on characteristics of its assets, proper asset management is critical to meet the needs of all stakeholders in the business. In this context, the productivity gain is a sine qua non for the survival of any company included in a scenario where the quality of energy supply, with appropriate costs, is the main goal. This work will address the use of Total Productive Management (TPM) methodology in an electricity distribution company for managing its assets, mainly in the maintenance and operation phases of its operating cycle. Thus, the current situation will be explored in the Brazilian electric sector and its main challenges, the current concept of the TPM methodology and the development of international norms in asset management since the creation of the British specification publicly available PAS 55, until the release of the new standard ISO 5500. We will evaluate the results of the implementation of the pillars autonomous maintenance, planned maintenance and specific improvement of Total Productive Management (TPM) in an electricity distribution company. They will also be addressed the requirements of the new standard ISO 55000 asset management that these pillars meet TPM and its contribution to an excellent management of the assets of a distributor of electricity. Finally, the results achieved by the company after two years of use of the TPM are shown.